2021
DOI: 10.1111/rda.13898
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and prediction of function of lncRNAs in the ovaries of low and high fecundity Hanper sheep

Abstract: Contents Litter size is an important trait that determines the production efficiency of sheep bred for meat. Its detailed investigation can reveal the molecular mechanisms that control the fecundity of sheep and possibly accelerate the breeding process of new varieties of sheep that have high prolificacy. Long non‐coding RNAs (lncRNAs) have proven to be an important factor in the regulation of follicular development. However, the mechanisms by which lncRNAs regulate litter size in sheep remain unclear. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Moreover, some DELs were enriched in several signaling pathways involved in female reproduction, including steroid biosynthesis, 33 prolactin, 34 Jak–STAT, 35 and Wnt signaling pathways, 36 suggesting that the DELs have specific roles in the regulation of follicular development and fecundity in Hu sheep. This observation is supported by the results of previous studies in which lncRNAs were shown to be possibly associated with fecundity in sheep or goats 10–14,16,17,19,37 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, some DELs were enriched in several signaling pathways involved in female reproduction, including steroid biosynthesis, 33 prolactin, 34 Jak–STAT, 35 and Wnt signaling pathways, 36 suggesting that the DELs have specific roles in the regulation of follicular development and fecundity in Hu sheep. This observation is supported by the results of previous studies in which lncRNAs were shown to be possibly associated with fecundity in sheep or goats 10–14,16,17,19,37 …”
Section: Discussionsupporting
confidence: 87%
“…This observation is supported by the results of previous studies in which lncRNAs were shown to be possibly associated with fecundity in sheep or goats. [10][11][12][13][14]16,17,19,37 In the current study, we characterized a novel transcript, lncRNA-412.25 (from >5 mm healthy follicles), which was expressed at significantly higher levels in the HPBB group than in the LPB+ or LPBB groups. A different expression pattern was observed in different-sized healthy follicles from Hu sheep.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Through miRNA and lncRNA analysis of FecB BB Small Tail Han sheep and FecB++ Dorset sheep, it was found the differentially expressed genes on cell apoptosis and proliferation were affected by gene mutation [2,3] and participated in progesterone mediated steroid biosynthesis and oocyte meiosis pathway [4]. Xist (loc101112291) and Gtl2 (loc101123329) were found to be highly expressed in Hanper sheep, suggesting the regulation of follicular development through methylation processes [5]. Mir-6404 and mir-29c are involved in the regulation of high and low fecundity in goats [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cells have different functions in the specific biological cycle of the ovary and contribute to the maturation of follicles [7]. Previous studies have taken the ovary as a whole [8,9]. Few studies have been conducted to investigate the effect of different cells in the ovary on reproductive performance.…”
Section: Introductionmentioning
confidence: 99%